Signaling Role of Glutamate in Plants - Qiu, Xue-Mei; Sun, Yu-Ying; Ye, Xin-Yu; Li, Zhong-Guang (Frontiers in Plant Science, 2020)
It is well known that glutamate (Glu), a neurotransmitter in human body, is a protein amino acid. It plays a very important role in plant growth and development. Nowadays, Glu has been found to emerge as signaling role. Under normal conditions, Glu takes part in seed germination, root architecture, pollen germination, and pollen tube growth. Under stress conditions, Glu participates in wound response, pathogen resistance, response and adaptation to abiotic stress (such as salt, cold, heat, and drought), and local stimulation (abiotic or biotic stress)-triggered long distance signaling transduction. In this review, in the light of the current opinion on Glu signaling in plants, the following knowledge was updated and discussed. (1) Glu metabolism; (2) signaling role of Glu in plant growth, development, and response and adaptation to environmental stress; as well as (3) the underlying research directions in the future. The purpose of this review was to look forward to inspiring the rapid development of Glu signaling research in plant biology, particularly in the field of stress biology of plants.